Penerapan Metode Tilawati dalam Pembelajaran Membaca Al-Qur'an pada Anak Usia Dini di RA Darul Ulum Mani'an Majungan Pademawu Pamekasan - Selfi Yatul Aini (Institut Agama Islam Negeri Madura, 2021)
This study aims to determine the implementation of the Tilawati Method in learning to read al-Qur’an in early childhood and the advantages and disadvantages of inhibiting and supporting factors in the RA Darul Ulum Mani’an Majungan Pademawu Pamekasan.This research uses a descriptive qualitative approach in the form of written words.Source of data used to obtain data through observation, interview and documentation. Interview is a question and answer session with face to face interviewed about the problem under study.Observation is a data collection technique that is done by conducting careful research and systematic recording. Documentation can be done by researchcers to obtain supporting data about the findings obtained in the field. Analysis of the data in this study researchers through several stages, namely data reduction, data presentation and drawing conclusions. While checking the data is done through an extension of participation, research perseverance and triangulation. In this study, researchers used source triangulation because there was not enough information to obtain one source.The results of this study indicate that:first, the application of the Tilawati method in RA Darul Ulum went well even though in fact there were still inhibiting factors but it did not become a major barrier to the application of the Tilawati method. Secondly, advantages the application of the tilawati method, namely balancing the learning approach classically and individually. The drawback is that for those who do not pass smoothly it will also take a long time because this method of passing is not determined by the month or year. Third, (a) supporting factor, easy method so that it does not make the child depressed. (b) inhibiting factors, lack of facilities so that using only one approach.